1H-NMR-Based Metabolomic Analysis of Cerebrospinal Fluid From Adult Bilateral Moyamoya Disease: Comparison With Unilateral Moyamoya Disease and Atherosclerotic Stenosis. Issue 17 (May 2015) - Jeon, Jin Pyeong; Yun, Taeho; Jin, Xing; Cho, Won-Sang; Son, Young-Je; Bang, Jae Seung; Kang, Hyun-Seung; Oh, Chang Wan; Kim, Jeong Eun; Park, Sunghyouk
Abstract : Abstract: Although metabolomics has been increasingly used to observe metabolic pattern and disease-specific metabolic markers, metabolite profiling for moyamoya disease (MMD) has not yet been done in adults. This study investigated cerebrospinal fluid (CSF) metabolites specific to bilateral MMD (B-MMD) and compared them to those of unilateral MMD (U-MMD) or atherosclerotic stenosis with hydrogen-1 nuclear magnetic resonance spectroscopy to identify metabolic biomarkers associated with MMD in adults. CSF samples of B-MMD (n = 29), U-MMD (n = 11), and atherosclerotic cerebrovascular disease (ACVD) (n = 8) were recruited. Principal component analysis, partial least square discriminant analysis, and orthogonal projections to latent structure discriminant analysis (OPLS-DA) were done for the comparisons. Diagnostic performance was acquired by prediction of 1 left-out sample from the distinction model constructed with the rest of the samples. B-MMD showed an increase in glutamine ( P  < 0.001) and taurine ( P  = 0.004), and a decrease in glucose ( P  < 0.001), citrate ( P  = 0.002), and myo-inositol ( P  = 0.006) than those in ACVD. U-MMD showed a higher level of glutamine ( P  = 0.005) and taurine ( P  = 0.034), and a lower level of glutamate ( P  < 0.004) than those in ACVD. No difference at the metabolite level was observed between B-MMD and U-MMD. Cross-validation with the OPLS-DA model showed a high accuracy for the prediction of MMD. The results of the study suggest that a metabolomics approach may be helpful in confirming MMD and providing a better understanding of MMD pathogenesis. Elevated glutamine in the CSF may be associated with MMD pathogenesis, which was different from ACVD. Abstract : Supplemental Digital Content is available in the text